Mitigasi COVID-19 di Pondok Pesantren X, Tangerang Selatan, Banten, Indonesia - Yusmar, Sherly Aini; Sari, Meliana (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2023)
AbstractCOVID-19 is a non-natural disaster that impacts various sectors. One of them is the education sector. Islamic boarding schools are one of the places where Covid-19 is transmitted during the pandemic. Among the efforts to minimize losses and impacts due to COVID-19 are mitigation efforts. Mitigation is a series of efforts to reduce disaster risk. Mitigation in this research uses the OHSAS 18001:2007 hierarchical approach. The aim of this research is to understand the description of the mitigation of the COVID-19 pandemic at Islamic Boarding School X. The study design in this research uses a mix method, with a sample size of 300 respondents and 1 key informant. Determination of the sample using proportionate stratified random sampling and determination of key informants using purposive sampling. The results of the research show that Islamic Boarding School In substitution, there are no activities carried out online. In technical control, there are only 2 of the 6 variables that comply with applicable regulations, namely vaccination and ventilation. In administrative control, only 1 of the 4 variables had a positive connotation, namely 93.3% of respondents who stated that the role of the COVID-19 task force was good. And the PPE hierarchy shows that 98.3% of respondents were found to be inappropriate in using masks. Therefore, in the current era of the Covid-19 epidemic, Islamic Boarding School The management of Islamic Boarding School.Keywords: COVID-19, Mitigation, Islamic Boarding School